Comparative analysis of international experience in assessing the financial efficiency of circular construction projects - Futnikov, V. (Ways to Improve Construction Efficiency, 2024)
The article presents a comprehensive systematic and comparative analysis of international experience in assessing the financial efficiency of circular construction projects. The study examines multiple empirical cases from the Netherlands, Switzerland, Finland, Sweden, Denmark, the United Kingdom, Poland, Germany, and Colombia, focusing on projects in both commercial and municipal sectors where circular economy principles were applied. The research identifies significant factors influencing the effectiveness of circular approaches, such as the institutional and regulatory environment, availability of secondary material infrastructure, market maturity of circular solutions, and local socio-economic conditions. Case studies demonstrate that the integration of classical and circular-oriented methods enables measurable improvements in project performance, including increased ROI, reduced payback periods, decreased LCC, and generation of indirect benefits such as enhanced indoor environmental quality, biodiversity preservation, and social inclusion. The analysis highlights geographical and contextual variability in financial outcomes, showing that countries with well-developed policies and waste management systems achieve higher benefits from circular construction initiatives compared to regions with limited secondary material reuse. Furthermore, the study illustrates the practical advantages of hybrid assessment models that integrate traditional financial analysis with circularity-focused indicators, enabling decision-makers to evaluate multiple dimensions of project value and avoid oversimplification of investment performance. By synthesizing lessons from international practice, the article provides a robust methodological framework for the adaptation of circular assessment tools to the Ukrainian construction sector, offering guidance for the development of flexible, context-sensitive investment evaluation models. The findings underline the potential for circular approaches not only to reduce environmental impact but also to enhance long-term economic efficiency, demonstrating that sustainable investment strategies can reconcile profitability with social and ecological considerations. This research contributes to the advancement of knowledge in construction finance, sustainability assessment, and circular economy implementation, providing empirical evidence for policymakers, investors, and practitioners seeking to implement financially viable and ecologically responsible construction projects.